Three‐Phase Current Control by Dynamic Reconstruction of Undetected Currents for AC Motor Drives. Issue 4 (March 2017) - SHINNAKA, SHINJI; ISHIDUKA, TAKUMI
SUMMARY: This paper proposes new three‐phase current control methods for AC motor drives, which detects only a phase current from among three‐phase currents. The first proposed method first detects a phase current, and then estimates the two‐phase current in the stationary reference frame using the detected single phase current. The second proposed method first detects a phase current, then synthesizes the two‐phase quasi‐current in the dq rotating reference frame, and finally produces two‐phase current estimates by extracting the positive‐phase component from the quasi‐current. The third proposed method produces two‐phase current estimates by filtering out the negative‐phase component from the quasi‐current. This paper presents the principles and detailed characteristic analyses of the proposed methods and validates them on the basis of extensive experiments.